ENVIRONMENTAL ISSUES AND ENERGY CONSERVATION IN BUILDINGS IN PAKISTAN: ROLE OF ARCHITECTURAL INTERVENTION - Arif, S.; Khan, A.; Alamgir, K. (The Nucleus, 2011)
Energy shortage and environmental catastrophe is the severe problem globally and particularly important for the developing countries like Pakistan. There is a serious need to solve the problem for a sustainable building environment as the building sector has become a major consumer of energy. An attempt has been made for the building professionals and building users for adherence into their design and construction the energy conservation measures to reduce environmental problems more easily after the thorough review of the famous authors’ research work and findings in this field. The ultimate aim is the establishment of awareness for the building professionals for delivering sustainable buildings in Pakistan. Through the implementation of design measures to mitigate the urban heat island, the general public can decrease their demand for energy and effectively cool the urban landscape. In addition to the economic benefits, energy conservation leads to reductions in CO2 emissions.